Benefits and shortcomings of decentralised forest management in Burkina Faso - Bouda, Z.H.N.; Tiveau, D.; Savadogo, P.; Ouédraogo, B. (Stellenbosch University, 2011)
Decentralization initiatives are on-going in many developing countries. In Burkina Faso, the government has embarked on a long-term decentralization effort that groups rural villages into self-governing communes with the capacity to plan their own development programs. Nearly two decades before this process, a system of joint forest management was introduced. The new form of administrative decentralization has impacted on joint forest management. This study sought to examine the effects of decentralization on joint forest management and the livelihoods of the rural poor. Information was obtained through semi-structured interviews, interviews with local forestry officials, direct observation, and by reviewing existing literature. The results indicated that administrative decentralization brings legality to joint forest management, which was already legitimated by local people. In return, joint forest management generates benefits to local people through socio-economic infrastructure, wood and non-wood forest products, to the local government through tax collection systems, and to the forest through some extent improved ecological sustainability. There were shortcomings however, such as land tenure insecurity, low local organizational capacity; lack of transparency in the wood fuel market, low level of diversification of the sources of revenue and weakness of local institution to implement their functions. Thus, a concerted effort should be made to manage the remaining natural forests through the development of appropriate strategies to empower local communities to manage and benefit from forest resources through the new arrangements for administrative decentralization. Caution is needed regarding transparency, financial and technical incentives and long-term commitment from the central government.